Pengaruh Retribusi Daerah Dan Pajak Daerah Terhadap Kapasitas Fiskal di Kabupaten Bogor Ditinjau Dari Perspektif Ekonomi Islam - Azhar, Zuhrotun Firdausi; Rahmawati, Desiana; Gunaepi, Aang (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of regional levies and regional taxes on fiscal capacity in Bogor Regency viewed from the perspective of Islamic Economics for the 2007-2021 period. The research method uses the classical assumption test, multiple linear regression, and hypothesis testing. This type research uses quantitative budget taken from the Central Statistics Agency (BPS) website. From the simultaneous test result, the first result is that there is no effect of receiving regional levies on Fiscal Capacity in Bogor Regency, secondly there is an effect of local tax revenues on Fiscal Capacity in Bogor Regency, thirdly there is an effect of receiving regional levies and local taxes simultaneously on Fiscal Capacity in the Regency Bogor. From the results obtained, it is hoped that the Bogor Regency government will focus on increasing regional retribution and regional tax revenues.